Effect of cutaneous Leishmaniasis infection on polymorphisms of IL-17A (rs2275913) - Ramzi, Ula Farooq; Saheb, Entsar Jabbar; Hussein, Watheq Muhammed (Iraqi Journal of Science, 2025)
Leishmaniasis, a disease triggered by the parasitic protozoan Leishmania, is spread through the bite of infected female sandflies, specifically those of the Phlebotomus and Lutzomyia species. The body's defense mechanisms, both innate and adaptive, rely heavily on cytokines, a category of glycoproteins or modulatory proteins that orchestrate a crucial response to infection and disease. This study aimed to elucidate the relationship between serum IL-17A levels and single nucleotide polymorphisms (SNP) of IL-17A (rs2275913) with the susceptibility to cutaneous leishmaniasis. A total 200 samples of whole blood were collected form patients and controls at Baquba Teaching Hospital /Diyala Governorate/ Iraq from October 2022 to February 2023 which were used to measure serum IL-17A level using enzyme-linked immunosorbent assay and IL-17A SNP using High Resolution Melting Technique. The results revealed no significant differences in serum IL-17A levels between patients with cutaneous leishmaniasis and controls. However, high serum levels of IL-17A for patients were detected when compared with controls. Notably, younger patients (ages 16-25 and 26-35) showed decrease mean levels IL-17A when compared with controls. While, an increase statistically of levels IL-17A for adults and elderly (46-55) and (56-65) years old for patients when compared with controls. Additionally, there was an observed increase in IL-17A of patients’ male versus with female compared with controls group. However, the distribution of serum IL-17A levels by SNP (rs2275913) demonstrated no differences between the genotypes of the groups. This study showed that the level of IL-17A was slightly elevated in patients when compared with controls. Interestingly, the results had revealed that the SNP for IL-17A (rs2275913) maybe a risk factor for susceptibility infection with cutaneous leishmaniasis, and considered the mutant allele A as a risk allele and genotype AA as more risk factor than the rest genotypes.